PERANCANGAN VISUAL IDENTITY TAS SYALUNA KOTA PAYAKUMBUH - ASEP HIDAYAT, Drs. Syafwan, M.Si., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Uniqueeshawls bag from Payakumbuh with knitting techniques, with knitted yarn material and available in various colors and can even be ordered according to the wishes of consumers. The advantages of this product are handmade products, which means that each bag is not the same, so that it becomes a special attraction for consumers, but there is no visual identity on product packaging, logos and the concept of visual identity that still does not exist.The design of Syaluna's visual identity bag can apply visual identity that attracts the attention of consumers and has long-term profitability to develop Syaluna's visual identity design goals are interesting and different from other competitors, and so that the Syaluna visual identity bag is good and effective so that it is preferred by consumers so that in the future it can reach the target market.The analytical method used is 5W + 1H analysis (what, who, where, when, why, and how) to find a solution to the problem at hand. The design process begins with observations, observations and interviews with the business owner of Tas Syaluna, in order to obtain the data needed in designing Visual Identity. Supporting media used to support the main media Manual Book include stationary, paper bag, T-shirt, sticker, poster, and x-banner.Keyword: Visual Identity, logo, tas rajut Syaluna